2019
DOI: 10.1021/acsami.9b04803
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Tissue-Level Characterization of a Medical Atmospheric Pressure Argon Plasma Jet

Abstract: Nonthermal treatment with cold atmospheric plasma (CAP) is a promising option for local treatment of chronic-inflammatory and precancerous lesions as well as various mucosal cancer diseases, besides its primary indication for wound healing and antiseptics. Atmospheric pressure plasma jets (APPJs) are versatile plasma sources, some of which are well-characterized and medically approved. The characterization of APPJs, however, is often based on the treatment of simple solutions or even studies on the plasma effl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…However, the induction of apoptosis was higher in CC cells compared to cells from healthy cervical tissue. The less significant apoptotic effect on non-cancerous cells is in line with an increasing number of studies utilizing APPJ, including our group [35,36]. Single cells were treated in suspension to avoid mechanical detachment and associated cell damage, as well as drying effects.…”
Section: Discussionmentioning
confidence: 61%
“…However, the induction of apoptosis was higher in CC cells compared to cells from healthy cervical tissue. The less significant apoptotic effect on non-cancerous cells is in line with an increasing number of studies utilizing APPJ, including our group [35,36]. Single cells were treated in suspension to avoid mechanical detachment and associated cell damage, as well as drying effects.…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, computer simulations showed that RNS reveal enhanced permeability through phospholipid bilayers compared to that of reactive oxygen species (ROS) [32]. Considering that elevated RONS levels overstrain the antioxidant resistance of cancer cells, MABS promises to be highly effective, as we found the reactivity of MABS significantly higher compared to the kINPen due to greater excitation of atoms measured by spatially resolved OES and higher levels of generated oxygen-centered radicals analyzed by ESR ( Figure 1) [19,21].…”
Section: Discussionmentioning
confidence: 77%
“…An increasing number of studies, however, reveal that healthy tissue is not as affected by apoptosis as critically as are malignant cells. Based on different apoptosis assays, our group recently showed that apoptosis cannot sufficiently explain the CAP-dependent inhibition of cell proliferation in primary human fibroblasts using an APPJ [19]. In line with this, Liedke et al showed similar apoptosis-independent cell effects on healthy mouse embryonic fibroblasts after treatment with an APPJ [28].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations